International law, the United Kingdom and decisions to deploy troops abroad - White, Nigel D. (Cambridge University Press, 2010)
Examines the role that international law plays in UK institutions of government when considering the deployment of armed forces to conflict and post-conflict zones. This is put into the context of the debate in the UK about the introduction of a War Powers Resolution.